A Target-Assignment Problem - Manne, Alan S. (Operations Research, 1958)
This paper is concerned with a target assignment model of a probabilistic and nonlinear nature, but nevertheless one which is closely related to the “personnel-assignment” problem. It is shown here that, despite the apparent nonlinearities, it is possible to devise a linear programming formulation that will ordinarily provide a close approximation to the original problem.